Tuned decoration of sodium montmorillonite (Na-MMT) nanoclay with MoSe2/RGO for enhancing microwave absorption - Mahdieh Dehghani-Dashtabi; Hoda Hekmatara; Masoud Mohebbi (Scientific Reports)
Abstract MoSe2/rGO/Na-MMTi (i = 0,15, 35, and 50 wt%) were named as m1, m2, m3 and m4, respectively, are novel microwave absorbing nanocomposites which consist of three porous contents with multiple dielectric junctions and unique 0D/2D/2D structure, were prepared via two-steps method. The results show, that MoSe2/rGO/Na-MMTi (i = 35%) nanocomposites demonstrated a minimum reflection loss (RLmin) of -76 dB at a thickness of 1.5 mm, with a dual bandwidth of 5.83 GHz, introduced as an optimal sample. The notable reflection loss and dual-band absorption at low thickness of MoSe2/rGO/Na-MMT nanocomposite are attributed to the synergistic effects of various factors, including porous and layered structure, heterogeneous interfaces, enhanced interface area in 0D/2D/2D structures, and the formation of defects, alongside surface polarizations. The finite-element stimulation proves that radar cross section (RCS) and far field of a typical perfect conductor (PEC) sphere reduced by 28-44dB and 16-20dB, respectively when it was covered with an specfic thickness of each nanocomposites.